A Comparison of Brook Trout Passage at Road Culverts to Broadscale Assessment Criteria in a Pennsylvania Headwater Stream. (23rd June 2021) - Rogers, Karli M.; Rummel, Shawn M.; Lavelle, Kathleen M.; Duchamp, Joseph E.; Niles, Jonathan M.; Janetski, David J.
Abstract: Restoring stream connectivity by replacing road culverts is a high conservation priority, yet long‐term fish passage data aimed to "ground‐truth" culvert prioritization methods are lacking. One common tool for prioritizing culvert removals is the protocol developed by the North Atlantic Aquatic Connectivity Collaborative (NAACC), which uses culvert characteristics to estimate barrier severity and fish passage. To determine the degree to which NAACC scoring reflects trout passage, we monitored Brook Trout Salvelinus fontinalis movements through three culverts and a reference site (no culvert) in a central Pennsylvania watershed. Passage was nearly continuously monitored for 16 months using remote stationary PIT tag readers. We found that NAACC ranks underestimated Brook Trout passage through two of three culverts. Specifically, the culvert with a rank of "reduced aquatic organism passage (AOP)" experienced higher rates of upstream passage (up to 10 upstream movements per day) than all other sites combined, including the reference site. The reduced AOP site also had a similar proportion of the tagged population that moved upstream (20.9%) compared to the reference site (16.9%). Of the two remaining culverts, both box culverts rated as "no AOP, " one had almost no upstream passage (only two upstream movements over the entire study) and the other had passage rates similar to the reference stream (up to four upstream movements per day). Brook Trout tended to move during high flow and the fall spawning period. We suggest that, for the streams considered in our study, the NAACC protocol may better predict upstream passage if it emphasizes culvert type and adjusts measurement thresholds in the AOP coarse screening. If these patterns are supported by studies at other locations, a more nuanced treatment of culvert type and outlet characteristics in NAACC protocols may more accurately predict Brook Trout passage through culverts.